Clinical outcomes and safety of 7-day versus 14-day antibiotic therapy for bloodstream infections in adults: A systematic review and meta-analysis with trial sequential analysis - Chen-Wei Wu; Chih-Cheng Lai; Jheng-Yan Wu; Mei-Chuan Lee (Journal of Infection and Public Health)
The optimal duration of antibiotic therapy for bloodstream infections (BSIs) remains uncertain. This meta-analysis with trial sequential analysis (TSA) compared the efficacy and safety of 7-day versus 14-day antibiotic courses in adults. A systematic search of PubMed, Embase, and Cochrane Library identified four randomized controlled trials (4794 patients). The 7-day course showed similar 90-day all-cause mortality (RR 0.94, 95 % CI 0.79–1.12, p = 0.51) and bacteremia relapse rates (RR 1.15, 95 % CI 0.80–1.64, p = 0.45) compared to 14 days. No significant differences were found in adverse events, including acute kidney injury, diarrhea, allergic reactions, and Clostridioides difficile infections. TSA indicated an insufficient information size. While 90-day mortality is an objective endpoint, it may not fully capture clinical recovery or long-term sequelae. Nonetheless, the findings indicate that a 7-day antibiotic course achieves outcomes comparable to a 14-day regimen in non–high-risk patients, supporting shorter durations consistent with antimicrobial stewardship.